HUBUNGAN DIABETES MELITUS GESTASIONAL TERHADAP KEJADIAN BERAT BADAN LAHIR RENDAH DI RSUD DR H ABDUL MOELOEK TAHUN 2023 - Suhaili, Gadis Bunga; Rukmono, Prambudi; Nareswari, Shinta; Sari, Ratna Dewi Puspita (CV. Jasa Sukses Abadi, 2024)
A low birth weight (LBW) infant is defined as an infant born weighing less than 2500 grams regardless of gestational age. The main factors causing LBW are maternal factors, fetal factors, and placental factors. Risk factors for LBW associated with maternal factors include a history of complications during pregnancy, one of which is gestational diabetes mellitus. This study used a cross-sectional design with Pearson Chi-Square statistical test conducted at Dr. H. Abdul Moeloek General Hospital, Lampung Province in October - November 2024. The study sample was infants born at Dr. H. Abdul Moeloek Hospital in the period January - December 2023. The results of this study indicate that 16% of infants born were extremely low birth weight (ELBW), 20% of infants born were very low birth weight (VLBW), and 64% of infants born were low birth weight (LBW). The results of the chi-square analysis showed that there was a relationship between gestational diabetes mellitus (p = 0.042) and low birth weight (LBW).